2018
DOI: 10.1016/j.joca.2018.02.385
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid fingerprinting in end-stage knee osteoarthritis: a novel biomarker concept to assess disease modifying therapies

Abstract: Purpose: Healthy cartilage homeostasis depends on an intact collagen scaffold and high aggrecan content. ADAMTS-5 (A Disintegrin And Metalloprotease with ThromboSpondin-motifs-5) is critically involved in arthritic diseases because of its direct role in cleaving aggrecan. Several studies indicate that inhibition of ADAMTS-5 may have the potential to stop progression of osteoarthritis (OA). In the present study, we investigated the in vitro efficacy of M6495, an inhibitor of ADAMTS-5, including assessment of af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Potential marker compounds for explaining the dependent Y-variables (pineapple varieties) were determined from VIP (variable importance in the projection values) [29]. VIP represents a degree of how much each variable contributes to the PLS-DA model and its importance in class separation of which, variables with VIP > 0.8 were significant for the overall model followed by moderately significant VIP (0.8 -0.5) and VIP < 0.5 indicated insignificant variables [30]. Variables with VIP higher than 0.80 for phenolic compounds and volatile organic compounds are summarized in Table 6 and 7, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Potential marker compounds for explaining the dependent Y-variables (pineapple varieties) were determined from VIP (variable importance in the projection values) [29]. VIP represents a degree of how much each variable contributes to the PLS-DA model and its importance in class separation of which, variables with VIP > 0.8 were significant for the overall model followed by moderately significant VIP (0.8 -0.5) and VIP < 0.5 indicated insignificant variables [30]. Variables with VIP higher than 0.80 for phenolic compounds and volatile organic compounds are summarized in Table 6 and 7, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…OA is a chronic, prevalent, debilitating joint disease characterized by progressive cartilage degradation, subchondral bone remodelling, bone marrow lesions, meniscal damage, and synovitis. 40,41 The molecular mechanisms underlying the progression of OA are still not fully understood, leading to a lack of effective treatment strategies. 5 A TGF-β1 receptor inhibitor, SB-505124, was recently demonstrated to markedly attenuate articular cartilage degradation in an OA mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The levels remain increased up to five years after injury, indicating persistent local inflammation, which may contribute to articular cartilage degradation, and subsequent OA. [44][45][46][47][48] An upright weightbearing MRI study showed increased tibiofemoral contact area within three years after ACL rupture, regardless of whether reconstruction had been undertaken. 49 We clearly must continue to investigate the optimal management strategies for ACL injuries, both in terms of the immediate treatment to avoid secondary damage, and to define the role of reconstruction and the best technique if surgery is undertaken.…”
Section: Is the Die Cast? Anterior Cruciate Ligament Injury And Osteo...mentioning
confidence: 99%